Improved reliability of AlGaN/GaN-on-Si high electron mobility transistors (HEMTs) with high density silicon nitride passivation - Sasangka, W. A. (2017)
We have systematically studied the effects of SixN1 − x passivation density on the reliability of AlGaN/GaN high electron mobility transistors. Upon stressing, devices degrade in two stages, fast-mode degradation and followed by slow-mode degradation. Both degradations can be explained as different stages of pit formation at the gate-edge. Fast-mode degradation is caused by pre-existing oxygen at the SixN1 − x/AlGaN interface. It is not significantly affected by the SixN1 − x density. On the other hand, slow-mode degradation is associated with SixN1 − x degradation. SixN1 − x degrades through electric-field induced oxidation in discrete locations along the gate-edges. The size of these degraded locations ranged from 100 to 300 nm from the gate edge. There are about 16 degraded locations per 100 μm gate-width. In each degraded location, low density nano-globes are formed within the SixN1 − x. Because of the low density of the degraded locations, oxygen can diffuse through these areas and oxidize the AlGaN/GaN to form pits. This slow-mode degradation can be minimized by using high density (ρ = 2.48 g/cm3) Si36N64 as the passivation layer. For slow-mode degradation, the median time to failure of devices with high density passivation is found to increase up to 2× as compared to the low density (ρ = 2.25 g/cm3) Si43N57 passivation. A model based on Johnson-Mehl-Avrami theory is proposed to explain the kinetics of pit formation.